Uso De La Virtualización Para Alta Disponibilidad Aplicada A Servidores Web De La Universidad Nacional De Trujillo - Monzón Llempén, Edwin Gerson (2017)
This research was conducted to provide High Availability to web servers of the National University of Trujillo through the use of virtualization, and to do a comparison was made between three of the leading data center virtualization platforms according to THE GARTNER MAGIC QUADRANT, the consultant and most prestigious research of information technologies; selecting the most appropriate to the requirements to ensure the continuity of services; This selection was made taking into account the IEEE 830 standard. At present there is no specific methodology to develop this type of research, however we chose to use the Cisco Lifecycle Services methodology, built according to the standards of Library Information Technology Infrastructure (ITIL); While Lifecycle Services is used to help install and operate successfully technologies cisco and optimize their performance throughout the lifecycle of a network, you can also fit any IT project that has to do with providing a service as it is made for improve Availability, scalability, security and stability of those services. It is for this reason and seeing the data center as a base platform where needed services are housed for the operations of the University that this methodology was chosen. To verify the results of our research performance testing of the proposed solution to observe their behavior in a high traffic services, with positive results and ensuring the continuity of services performed; there is obviously a limit to the HIGH AVAILABILITY of services and hardware with which currently University.